Creative decision making and visual search behavior in skilled soccer players - Roca, A.; Ford, P. R.; Memmert, D. (PLOS ONE, 2018)
The ability to produce creative solutions is a key part of expert performance. The aim of this study was to identify the visual search behaviors that underpin superior creative performance of skilled soccer players during simulated 11-a-side match play. Players (N = 44) were required to interact with a representative life-size video-based simulation of attacking situations whilst in possession of the ball. Clips were occluded at a key moment and they were required to play the ball in response to each situation presented. Moreover, they were required to name other additional actions they could execute for each situation. Creative performance on the task was measured using the three criteria of originality, flexibility, and fluency of decisions. Visual search behaviors were examined using a portable eye-movement registration system. Players were classified as most- (n = 11) or least-creative (n = 11) based on their performance on the representative task. The most-creative players produced more appropriate, original, flexible, and fluid decisions compared to least-creative players. The creativity-based differences in judgment were underpinned by differences in visual search strategy. Most-creative players employed a broader attentional focus including more fixations of shorter duration and towards more informative locations of the display compared with least-creative players. Moreover, most-creative players detected teammates in threatening positions earlier in the attacking play. Creative performance is underpinned by different underlying visual processes when compared to less-creative performance, which appears to be crucial in facilitating more creative solutions.